Association of medial gastrocnemius adiposity with poststroke severe malnutrition and functional performance of activities of daily living in older patients: A prospective analysis. (16th August 2022) - Shimizu, Akio; Nozoe, Masafumi; Ohno, Tomohisa; Nomoto, Akiko; Shigematsu, Takashi; Fujishima, Ichiro
Abstract: Background: Relationships among medial gastrocnemius intramuscular adipose tissue, nutrition status, and functional outcomes of patients after a stroke are unknown. This study was conducted to determine the relationship between nutrition status and gastrocnemius intramuscular adipose tissue and whether medial gastrocnemius intramuscular adipose tissue affects functional outcomes of older patients after a stroke. Methods: This prospective cohort study included 217 patients with stroke. Nutrition status was evaluated by the Global Leadership Initiative on Malnutrition. The medial gastrocnemius intramuscular adipose tissue was assessed using ultrasound echographic intensity. Multivariate linear regression analysis was used to determine the relationship between nutrition status at admission and medial gastrocnemius intramuscular adipose tissue. Furthermore, we examined the influence of medial gastrocnemius intramuscular adipose tissue on the Functional Independence Measure (FIM)–motor score at discharge and FIM‐motor efficiency, which indicates FIM‐motor changes during the hospital stay. Results: Severe malnutrition had a positive influence on medial gastrocnemius intramuscular adipose tissue on the nonparalyzed side ( β  = 0.175; P  = 0.044). Additionally, the medial gastrocnemius intramuscular adipose tissue on the nonparalyzed side was negatively correlated with the FIM‐motor score at discharge ( β  = −0.102; P  = 0.005) and FIM‐motor efficiency ( β  = −0.273; P  = 0.005). Conclusions: This study clarified the factors that contribute to a higher medial gastrocnemius intramuscular adipose tissue content on the nonparalyzed side and the effect of the higher adipose tissue content on functional outcomes.